The application of integral system of financial information in public budgets (2015)
The financial situation of any public or private organization is a basic consuming processes for decision making at all levels and in general a critical element to evaluate their management; Public administrations are in turn a paradigm of complex organizations, given its size and because single out in its organizational development of very specific functions, defined by rules that create rights and obligations determining your financial reality. That is why the public administration makes urgent the application of a managerial guidance to government management that generates complete, reliable and timely information regarding the handling performed within administrations in what refers financially. Well born FINANCIAL INFORMATION SYSTEMS INTEGRATED SIIF, which are an initiative of the Ministry of Finance and Public Credit that seeks to renew technologically and functionally and institutionally strengthen the finances and management of our national budget